2021
DOI: 10.1111/obes.12444
|View full text |Cite
|
Sign up to set email alerts
|

Euro Area Income and Wealth Effects: Aggregation Issues*

Abstract: This empirical study for private consumption in the euro area and the four largest euro area countries validates the need to separate components of income and supports the common practice to split wealth. A focus on income and wealth components avoids an aggregation bias in estimated income and wealth effects. It finds little evidence in favour of an extensive country aggregation issue given direct euro area estimates of income and wealth propensities and forecasts for consumption are not too different from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…See Frayne et al (2022) for an in-depth analysis of housing affordability in the Euro area. 3 The selection criteria employed in this paper are along the lines of the subset selection procedure used by de Bondt et al (2020de Bondt et al ( , 2021 for private consumption. 4 Initial visual inspection of the scree plot of the ordered eigenvalues suggests choosing between 3 and 7 factors depending on the country.…”
Section: Orcidmentioning
confidence: 99%
See 2 more Smart Citations
“…See Frayne et al (2022) for an in-depth analysis of housing affordability in the Euro area. 3 The selection criteria employed in this paper are along the lines of the subset selection procedure used by de Bondt et al (2020de Bondt et al ( , 2021 for private consumption. 4 Initial visual inspection of the scree plot of the ordered eigenvalues suggests choosing between 3 and 7 factors depending on the country.…”
Section: Orcidmentioning
confidence: 99%
“…For forecasters and analysts, housing investment is a significant and volatile component of aggregate demand (Nguyen, 2013) and an important driver of the business cycle (Huang et al, 2020;Leamer, 2015;Piazzesi & Schneider, 2016), including for the prediction of recessions (Aastveit et al, 2019;Kohlscheen et al, 2018). Changes to housing wealth have significant implications for private consumption spending (de Bondt et al, 2020(de Bondt et al, , 2021, and, as the Great Recession of 2008-09 has shown once again, housing booms usually develop into a recession, and when combined with a credit boom, they predict a harder landing (Cerutti et al, 2017). For monetary policymakers, the transmission of policy changes into lending rates and, via housing investment and house prices, into economic activity is as much of importance as the interaction between housing markets and the credit cycle for macroprudential policies (European Systemic Risk Board, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation